Chemodectoma in a Dog - Feitosa, Roseane Oliveira; Gonçalves, Saulo Romero Felix; Nascimento, Janilene De Oliveira; De Sena, Diana Guiomar Ferreira; Santos, Edna Michelly De Sá; Pereira, Marcia de Figueiredo; Junior, Valdemiro Amaro da Silva (Acta Scientiae Veterinariae, 2021)
Background: The chemodectoma is a rare neoplasm that originates from chemoreceptors located mainly in the aortic body, and carotid body and sinus, and responsible for detecting variations in blood pH, oxygen pressure and carbon dioxide. Dogs of brachiocephalic breeds and aged between 7 and 15 years have greater propensity. A neoplasm involves infiltrative growth in the vessels at the heart base, which leads to Congestive Heart Failure (CHF). The definitive diagnosis is performed by histopathological and/or immunohistochemical examination. The aim was to report a case of chemiodectoma in a dog, showed the disease clinical characteristics. Case: A 13-year-old male undefined breed dog was examinated in the medical clinic of small animal of Veterinary Hospital, Federal Rural University of Pernambuco (UFRPE) with respiratory effort, hyporexia, and edema in face, cervical, ventral thorax and thoracic limbs, with thirty days evoluted. About physical examination, we observed cachexia, orthopneic position, cyanosis and edema with a positive Godet sign, as well as 8% dehydration degree. Thoracic auscultation presented mixed dyspnea and muffled heart sounds. Chest radiography detected an radiopacity increase in pulmonary section and metastatic neoplastic process associated with pleural and pericardial effusion. Fluid therapy with lactated ringer and posterior thoracentesis in the right hemithorax region was performed for greater respiratory comfort for the patient. Hematological count and biochemical profiles stated normochromic normocytic anemia, relative and absolute lymphopenia, thrombocytopenia, as well as increased alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The patient died after 12 hours when was submitted to necroscopic examination and histopathological evaluation. An infiltrative tumor of cardiac base was observed invading the light of the right atrium, obstructing the venous return, as well as a large thrombus located in the left ventricle and diffuse nodules in the lungs. Hydrothorax and hydroperitoneum were observed with serous fluid, with hepatic, renal and brain congestion, and duodenum hemorrhage. Histologically, the tumor was characterized as a chemodectoma with pulmonary metastasis. Discussion: Cardiac tumors are uncommon for canine population. A study sampled 729,265 dogs with observed incidence reaching 0.19%. The most common type is hemangiosarcoma with 69%, followed by chemiodectoma and lymphoma. Authors describe predisposed brachycephalic breeds such as Boxer, Boston Terrier and French Bulldog. In our case, the patient had elongated snout and undefined breed. Deregulation of chemoreceptors, which detect changes in pH and partial oxygen and carbon dioxide pressures, can result in hyperpnea and dyspnoea. Edema represents a deficit in venous return from the cranial and cervical regions, with consequent increase in hydrostatic pressure and liquid leakage into the thoracic cavity and subcutaneous tissue, thus inferring the Caudal Vena Cava Syndrome (CVCS). Tumors from the cardiac base, integrated with the large arteries insertion and adjacent to the atria, can cause pericardial effusion observed in this case. Chemodectomas are described as essentially benign tumors with low metastatic potential. In this case, pulmonary metastasis was detected. Surgical treatment is recommended when feasible. In this case, the patient had late veterinary care, in addition to the contraindication for surgery by the lung metastasis presence.